The Disappearance of the Coxoh town of Escuintenango, Chiapas, 16th-19th Centuries - Martínez González, Alma Rosa (2022)
This article aims to expose the reasons for the disappearance of Escuintenango, Chiapas, Mexico, a Coxoh-speaking Mayan town. This population, whose importance laid mainly in being part of the Camino Real to Guatemala –essential for communication at the time– disappeared, leaving only ruins among fields of cattle. This work is the result of the examination of documents from the 16th to the 19th centuries found in the Archivo Histórico Diocesano of San Cristóbal de Las Casas. These documents revealed the demographic problems of Escuintenango, and the continued disposition of the authorities to prevent its disappearance. From this research, it was possible to conclude that its disappearance was a long-term process that responded to several factors, among which were: the inhospitable nature of the settlement area caused by the constant floods, the migration of its inhabitants to more prosperous places, such as Soconusco, the growing boom in cattle ranches, epidemics, and labor exploitation.